Negotiated authoritarianism: older people's associations and social governance in contemporary China - Robins, V (2018)
This study seeks to explore the role of older people's associations (OPAs) in 'social governance' in rural China. Specifically, it examines the role OPAs play in mediating disputes and implementing contentious policy at the grassroots. Previous studies of OPAs' role in grassroots politics have provided 'top-down', state-directed accounts of their activities. Yet these approaches overemphasise the state's role in such processes and passivize the agency of societal actors. Building on Joel Migdal's State-in-Society approach, this study will provide a more dynamic prism through which to view this topic, arguing that just as the state affects society, the reverse is also true. Specifically, this study will seek to understand how OPAs respond to the kinds of authority and obligations that local states channel through them, and ask whether such interactions provide OPAs with an opportunity to negotiate with officials over the outcomes of state policy. This study hypothesises that reliance on OPAs for stability maintenance will provide elderly actors with leverage to negotiate with the state. This study is relevant for understanding authoritarian resilience at China's rural grassroots, and for addressing questions about stat-society relations in China, in particular whether the Party-state can continue to mobilise the social energy of local communities without weakening its grip on power. This study draws on over 23 months of fieldwork in Beijing, Fujian Yunnan, and Shaanxi between 2012 and 2016. It has engaged in long-term participant observation in 30 rural villages and has drawn on 176 structured interviews, 115 semi-structured interviews and 21 focus groups.